Cams and Pincer Impingement Are Distinct, Not Mixed: The Acetabular Pathomorphology of Femoroacetabular Impingement - Cobb, Justin (Springer-Verlag, 2010)
BACKGROUND: Many impinging hips are said to have a mix of features of femoral cam and an overcovered acetabulum causing pincer impingement. Correction of such a mixed picture by reduction of the cam lesion and the acetabular rim is the suggested treatment. QUESTIONS/PURPOSES: We therefore asked two questions: (1) Is the acetabulum in cam impingement easily distinguishable from the pincer acetabulum, or is there a group with features of both types of impingement? (2) Is version or depth of socket better able to distinguish cam from pincer impingement? METHODS: We analyzed the morphologic features of the acetabulum and rim profile of 20 normal, healthy hips, 20 with cams and 20 with pincers on CT. Pelvises were digitized, orientated to the best-fit acetabular plane, and a rim profile was plotted. RESULTS: Cam hips were shallower than normal hips, which in turn were shallower than pincer hips (84° ± 5° versus 87° ± 4° versus 96° ± 5°, respectively). The rim planes of cam, normal, and pincer hips had similar version (23°, 24°, 25°), but females were 4° more anteverted than males. CONCLUSIONS: We concluded cam and pincer hips are distinct pathoanatomic entities. Cam hips are slightly shallower than normal, whereas pincers are deeper. CLINICAL RELEVANCE: Before performing surgery for cam-type femoroacetabular impingement, surgeons should consider measuring the acetabular depth. The cam acetabulum is shallower than normal and may be rendered pathologically shallow by acetabular rim resection leading to early joint failure.